Utilization of Social Media (Instagram, Twitter and Facebook) as Educational Means Regarding Beauty Standards in the You're Enough Program - Yuda Pratama, Muhammad; Rifky Fadhillah, Febian; Mandela, Dohan (Educationist: Journal of Educational and Cultural Studies, 2023)
The beauty standard created is a reinforcement of the media, one of which is social media. Social media influences shaping beauty standards which then generalizes the perception of the Indonesian people about the concept of "beautiful". This makes beauty no longer a relative thing but has become a universal thing. Especially on social media, existence is the main goal where everyone wants recognition, likes and appreciation from others. The existence of this Beauty Standard can affect a person's psychosocial condition. The method implemented in this activity is a media-based strategy, which means this activity is a social media campaign. The purpose of holding this program is to educate young people about beauty standards through the Your Enough program campaign activities on social media.